ANTIMICROBIAL STEWARDSHIP STRATEGY TO REDUCE LENGTH OF STAY AND COST OF ANTIBIOTIC CONSUMPTION: A SYSTEMATIC REVIEW - Anak Agung Istri Agung Sri Stuti Damayanti; Ida Bagus Nyoman Maharjana; Atik Nurwahyuni (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Reducing the cost of care and length of stay for patient in hospital are important to monitor the benefits of implementing an antimicrobial management program. An antimicrobial management program is a strategy to decrease Antimicrobial Resistance (AMR) that affect to the treatment of the patient. One of the antimicrobial management programs is Antimicrobial Stewardship Programs (ASP). This study aims to determine the appropriate strategies in the application of Antimicrobial Stewardship Programs (ASP) that can reduce the length of stay and cost of antibiotic consumption for patient in hospital. Methods: This study was a systematic review that used PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidelines. Data obtained from Electronic databases ProQuest and Medline (PubMed) that published five years times span. By using keywords such as antimicrobial stewardship, antimicrobial resistance, length of stay, length of the hospital and patient cost to find the relevant journal. Results: The search found 3,541 studies, of which 26 studies were included in the systematic review. After excluded the article review, there were 9 studies that used quasi-experimental, observational cohort studies and Randomized Control Trial (RCT). These studies conducted majority in Europe and USA, only 1 study that conducted in Asia. Analysis of the studies found out that 6 of 9 studies mentioned if ASP can reduce the length of stay of the patient in hospital. Only 3 of 9 studies that examined the effect of ASP in cost of care and these 3 studies mentioned ASP can reduce the cost of care. Conclusion: This study showed that implementing ASP can reduced the length of stay and antibiotics consumption among patient in hospital by manage the antimicrobial use, conduct audits and feedback in an appropriate step, and intravenous to oral switch program. Keywords: Antimicrobial stewardship, length of stay, cost of care